SELF-ESTEEM MECHANISM BASED ON WORKPLACE SANCTITY AND INSTITUTION LINKING ORGANISATIONAL CITIZENSHIP BEHAVIOURS TO SPIRITUAL LEADERSHIP AND ROLE OF MEDIA IN PORTRAYING WOMEN LEADERS AS AN ARBITRATOR - Manzoor, Dr. Seema; Khan, Muhammad Kamran; Idrees, Dr. Nusrat (Journal of Peace, Development and Communication, 2022)
The purpose of this research is to find the relationship between “organizational citizenship behaviour (OCB) and spiritual leadership (SL)” with the help of two arbitrating variables “organization-based self-esteem (OBSE) and workplace spirituality (WPS)”. Along with that, the study has also focused on the role of media regarding women leaders as a moderator through the relationship of variables spiritual leadership and workplace spirituality. In this research, the researcher has used a questionnaire as a tool to collect data from the selected sample. In addition, this study has used the “Partial least squares-structural equation modeling (PLS-SEM) technique” for the analysis of data. Here the sample (220 participants) has been chosen from the Islamic educational institute Indonesia including their teaching faculty and educational staff. Eight hypotheses were proposed in this study and out of which only five were accepted on the basis of results. The OBSE acts as a motivational force in establishing a relationship between the variables SL and OCB. We see the lacking of adopting literature on the spiritual relationship in religious academic institutions limits the arguments on the scope of the study system. On the basis of this research, among Muslim teachers, the correlation between SL and OCB has been derived. Though in leadership an ample amount of research has adopted many theories based on leadership and the research facts have changed the prominence of spiritual leadership as the key factor of influence in religious institutions and based on flexible behaviours, following SL has emerged as key determinant in religious institutions. Therefore, the importance of teaching faculty with flexible behaviours has increased in religious institutions and as a result correlation between OCB and OBSE is identified through SL. This will help to enhance the follower’s development of social and basic well-being through the development of common goals and vision to provide a sense of achievement on an individual level and a sense of appreciation at the collective level. This study increases the knowledge at the academic level regarding the role of SL which, is rapidly growing and gaining importance and is relatively new for the academicians and at the managerial level. Thus as a result it influences the teaching faculty and the academic staff both at the theory and practical levels.